2021
DOI: 10.1371/journal.pone.0248010
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and surgical care of retinal detachment during the first SARS-CoV-2 lockdown period at a tertiary referral center in Austria

Abstract: Purpose To assess the influence of the SARS-CoV-2 lockdown in spring on frequency, severity and quality of care of rhegmatogeneous retinal detachments (RRD) in a tertiary referral center in Vienna, Austria. Methods Single center, consecutive case series with historical controls. Patients presenting with primary RRD during the first Austrian SARS-CoV-2 lockdown (March 16th–May 3rd 2020) and a corresponding control group consisting of the same time period of the preceding 3 years. Results The mean number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…71 While there was a 81% reduction in glaucoma outpatient visits in India, there was a 62% increase in the proportion of glaucoma emergencies. 72 Some studies found a 55-80% decrease in retinal detachment repairs during lockdown periods in 2020, 73,74 but others found a 39% increase for urgent surgeries, such as retinal tears, retinal detachments, and trauma. 75 One study of 82 patients with rhegmatogenous retinal detachments at Wills Eye Hospital found that the patients in 2020 tended to present later than in prior years (20% within a day vs 37%, respectively, P=0.005), were less likely to have their maculas still attached (24% vs 50%, P=0.001), had worse presenting visual acuities (1.00logMAR vs 0.48logMAR, P=0.008), and were more likely to have grade C proliferative vitreoretinopathy (13% PVR vs 5%, P=0.03).…”
Section: Ocular Emergencies and Effects Of Delayed Carementioning
confidence: 99%
“…71 While there was a 81% reduction in glaucoma outpatient visits in India, there was a 62% increase in the proportion of glaucoma emergencies. 72 Some studies found a 55-80% decrease in retinal detachment repairs during lockdown periods in 2020, 73,74 but others found a 39% increase for urgent surgeries, such as retinal tears, retinal detachments, and trauma. 75 One study of 82 patients with rhegmatogenous retinal detachments at Wills Eye Hospital found that the patients in 2020 tended to present later than in prior years (20% within a day vs 37%, respectively, P=0.005), were less likely to have their maculas still attached (24% vs 50%, P=0.001), had worse presenting visual acuities (1.00logMAR vs 0.48logMAR, P=0.008), and were more likely to have grade C proliferative vitreoretinopathy (13% PVR vs 5%, P=0.03).…”
Section: Ocular Emergencies and Effects Of Delayed Carementioning
confidence: 99%
“…Most published reports of referrals due to RRD during the pandemic centred around the early impact of the first wave. [6][7][8][9][11][12][13][14]17,[21][22][23] To the best of our knowledge, this is the first study to analyse the yearto-year changes in the referrals due to RRD and to verify whether the number and characteristics of patients admitted with this condition changed across the three waves of the COVID-19 pandemic. We also verified whether the periodical lifting of epidemic restrictions was associated with a rebound effect on the referrals.…”
Section: Introductionmentioning
confidence: 99%
“…A retinal expert or a general ophthalmologist, trained to evaluate disease-specific markers biomicroscopically, might be flooded with additional information provided by the new systems. Especially in times of rising numbers of intravitreal injections, 67 or during the COVID-19 pandemic, 68 a retinal outpatient clinic must strive for the best of care for the individual patient. Telemedicine and real-time evaluation of patients have therefore become even more important.…”
Section: Discussionmentioning
confidence: 99%